Formal ontologies meet industry : 7th International Workshop, FOMI 2015, Berlin, Germany, August 5, 2015, Proceedings /: 7th International Workshop, FOMI 2015, Berlin, Germany, August 5, 2015, Proceedings. (2015) - Unknown
No abstract available